Modulation of apoptosis‐related microRNAs following myocardial infarction in fat‐1 transgenic mice vs wild‐type mice. Issue 11 (14th September 2018) - Ma, Huan; Chen, Peipei; Sang, Chuanlan; Huang, Daozheng; Geng, Qingshan; Wang, Lei
Abstract: Background: microRNAs (miRNAs) post‐transcriptionally regulate cardiac repair following myocardial infarction (MI). Omega‐3 polyunsaturated fatty acid (ω‐3 PUFAs) may support cardiac healing after MI, but the mechanism is unclear. Methods: The fat‐1 transgenic mouse expresses a ω‐3 fatty acid desaturase which converts ω‐6 PUFAs to ω‐3 PUFAs in vivo. MI was induced in fat‐1 transgenic (n = 30) and wild‐type (WT) mice (n = 30) using permanent ligation. Other transgenic and WT mice underwent sham procedure (n = 30 and n = 30, respectively). One week after occlusion, cardiac function was measured by echocardiography and the infarct size was assessed using histology and miRNA microarray profiling. Expression of selected miRNA was confirmed using quantitative real‐time PCR. Results: One week following MI, the fat‐1 transgenic myocardium had better cardiac function, a smaller fibrotic area, and fewer apoptotic cardiomyocytes than WT myocardium. Post‐MI profiling showed 33 miRNAs that were significantly up‐regulated, and 35 were down‐regulated, in fat‐1 group compared to the WT group (n = 3 and n = 2 mice, respectively). Among selected apoptosis‐associated miRNAs, 9 miRNAs were up‐regulated (miR‐101a‐3p, miR‐128‐3p, miR‐133a‐5p, miR‐149‐5p, miR‐192‐5p, miR‐1a‐3p, miR‐208a‐3p, miR‐29c‐5p, miR‐30c‐2‐3p), and 3 were down‐regulated (miR‐210‐3p, miR‐21a‐3p, miR‐214‐3p) in fat‐1 transgenic mice compared with WT mice. Kyoto encyclopaedia of genes and genomes (KEGG) pathway analysis indicated likely roles for these miRNAs in MI. Furthermore, Bcl‐2 expression was increased, and caspase‐3 decreased, in infarcted fat‐1 transgenic mouse hearts compared to WT hearts. Conclusions: ω‐3 PUFAs may have a protective effect on cardiomyocytes following MI through their modulation of apoptosis‐related miRNAs and target genes.